The figure of Bartolomé Finizola Celli in the background of Cardiovascular Program of Lara State (Revista Venezolana de Salud Pública, 2018)
We present a network of indirect and direct relationships between important persons in Venezuelan medicine since the early twentieth century and Bartolomé Finizola Celli, founder of the Cardiovascular Program of the Lara state. These relationships began with Dr. Luis Razetti and his legacy that goes through time by his disciples. We describe the events and personalities that influenced Dr. Bartolomé Celli during three periods of his life: university medical studies, practice in the rural areas and postgraduate cardiology studies. We highlight the lessons learned in each period, maintaining the basic doctrine as a fundamental condition.
Keywords: Venezuela; Cardiovascular; History